Consumer‐orientated development of hybrid beef burger and sausage analogues. Issue 4 (3rd May 2017) - Neville, Michelle; Tarrega, Amparo; Hewson, Louise; Foster, Tim
Abstract: Hybrid meat analogues, whereby a proportion of meat has been partially replaced by more sustainable protein sources, have been proposed to provide a means for more sustainable diets in the future. Consumer testing was conducted to determine consumer acceptability of different formulations of Hybrid beef burgers and pork sausages in comparison with both meat and meat‐free commercial products. Acceptability data were generated using the 9‐point hedonic scale. Check‐all‐that‐apply (CATA) questioning was used to determine the sensory attributes perceived in each product as well as information on the attributes of consumers' ideal products. It was identified that Hybrid products were generally well liked among consumers and no significant differences in consumer acceptability (p > .05) were identified between Hybrid and full meat products, whereas meat‐free products were found to be less accepted. However, Hybrid sausages received higher acceptability scores (6.00–6.51) than Hybrid burgers (5.84–5.92) suggesting that format may have a large impact on consumer acceptability of Hybrid products. Correspondence Analysis (CA) indicated that Hybrid products were grouped with meat products in their sensory attributes. Penalty analysis found that a "meaty flavor" was the largest factor driving consumer acceptability in both burgers and sausages. Cluster analysis of consumer acceptability data identified key differences in overall acceptability between different consumer groups (consumers who only eat meat products and consumers who eat both meat and meat‐free products). The Hybrid concept was found to bridge the acceptability gap between meat and meat‐free products; however, further product reformulation is required to optimize consumer acceptability. Abstract : Hybrid meat products could provide consumers with a healthy and convenient way to reduce their meat consumption. Consumer testing among predominantly meat eaters revealed that Hybrid meat products achieved a higher consumer acceptance than commercial vegetarian meat analogues. In addition, sensory characterization identified that such products shared similar sensory properties to full meat products.